Synthesis, Characterization, and In Vitro and In Silico Biological Evaluation of Novel Polyphenols Bearing a Quinazolin-4(3H)-one Ring as Promising Anti-Prostate-Cancer Agents - Şenol, Halil; Çağman, Zeynep; Çakır, Furkan; Tokalı, Feyzi Sinan (Synlett, 2025)
In this study, 12 novel polyphenols containing the quinazolin-4(3H)-one ring were synthesized and characterized using 1H/13C NMR and HRMS analyses, yielding the target compounds in excellent yields (88–96%). Biological evaluation revealed significant cytotoxic activity against PC3 prostate cancer and 3T3 fibroblast cell lines, with compounds 2,2′-(propane-1,3-diyl)bis-3-(2,4-dihydroxybenzylideneamino)quinazolin-4(3H)-one (5) and 2,2′-(propane-1,3-diyl)bis-3-(2,3,4-trihydroxybenzylideneamino)quinazolin-4(3H)-one (6) demonstrating the highest anticancer potential. Compound 6 exhibited the highest selectivity (IC50 = 5.72 µM, SI = 68), outperforming the reference drug, doxorubicin. In silico studies, including molecular docking and dynamics simulations, showed strong binding affinities for mTOR, P110α, and PARP1, particularly for compound 6. Key interactions, such as hydrogen bonds and π-π stacking, contributed to the stability of the 6–mTOR complex. These results highlight compounds 5 and 6 as promising candidates for prostate cancer therapy, with compound 6 showing superior selectivity and interaction profiles, providing the groundwork for further preclinical development.
Keywords: hydrazone; quinazolin-4(3H)-one; prostate cancer; cytotoxicity; molecular docking; molecular dynamics